Identification of new genomospecies in the mycobacterium terrae complex - Yun Fong Ngeow; Yan Ling Wong; Joon Liang Tan; Kar Wai Hong; Hien Fuh Ng; Bee Lee Ong; Kok Gan Chan (2015)
Members of the Mycobacterium terrae complex are slow-growing, non-chromogenic acidfast bacilli found in the natural environment and occasionally in clinical material. These genetically closely-related members are difficult to differentiate by conventional phenotypic and molecular tests. In this paper we describe the use of whole genome data for the identification of four strains genetically similar to Mycobacterium sp. JDM601, a newly identified member of the M. terrae complex. Phylogenetic information from the alignment of genomewide orthologous genes and single nucleotide polymorphisms show consistent clustering of the four strains together with M. sp. JDM601 into a distinct clade separate from other rapid and slow growing mycobacterial species. More detailed inter-strain comparisons using average nucleotide identity, tetra-nucleotide frequencies and analysis of synteny indicate that our strains are closely related to but not of the same species as M. sp. JDM601. Besides the 16S rRNA signature described previously for the M. terrae complex, five more hypothetical proteins were found that are potentially useful for the rapid identification of mycobacterial species belonging to the M. terrae complex. This paper illustrates the versatile utilization of whole genome data for the delineation of new bacterial species and introduces four new genomospecies to add to current members in the M. terrae complex.